2010
DOI: 10.1111/j.1440-1827.2010.02561.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence in situ hybridization analysis with a tissue microarray: ‘FISH and chips’ analysis of pathology archives

Abstract: Practicing pathologists expect major somatic genetic changes in cancers, because the morphological deviations in the cancers they diagnose are so great that the somatic genetic changes to direct these phenotypes of tumors are supposed to be correspondingly tremendous. Several lines of evidence, especially lines generated by high-throughput genomic sequencing and genome-wide analyses of cancer DNAs are verifying their preoccupations. This article reviews a comprehensive morphological approach to pathology archi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…50 lg of cell lysates were add to the reaction buffer (80 mM Tissue microarray (TMA), immunohistochemistry and western blotting. Details on TMA construction and immunohistological evaluation are based on previous literature (23) and in the Supporting Information. Briefly, the expression of LPCAT4 in CRC was categorized according to the modified algorithm in previous literature, that is, the staining intensities were categorized as follows: blue (0); blue-brown (1); brown (2); and bright brown (3).…”
Section: Methodsmentioning
confidence: 99%
“…50 lg of cell lysates were add to the reaction buffer (80 mM Tissue microarray (TMA), immunohistochemistry and western blotting. Details on TMA construction and immunohistological evaluation are based on previous literature (23) and in the Supporting Information. Briefly, the expression of LPCAT4 in CRC was categorized according to the modified algorithm in previous literature, that is, the staining intensities were categorized as follows: blue (0); blue-brown (1); brown (2); and bright brown (3).…”
Section: Methodsmentioning
confidence: 99%
“…Clinicopathological information on EPHB3 alone (not accompanied with EPHB2) in human gastrointestinal tract cancers remains limited. A clinical interpretation of the over-expression and/or amplification of EPHB3 (Figure 1) in gastrointestinal cancer [70,71] awaits further investigations.…”
Section: Ephb3mentioning
confidence: 99%
“…Human archival tissue blocks contain specimens of human tumors in various stages of development, which are precious in the post-human-genome-sequencing era. Based on their findings and other's work, Sugimura et al (Sugimura, Mori et al 2010) stated that the intensive application BAC clones as probes for FISH that have exact 'addresses' in the whole genome will become a useful diagnostic tools for pathologists. Thousands of BAC clones are commercially available, and any of them can be used as FISH probes.…”
Section: Fluorescence In Situ Hybridization (Fish) Analysis Of Patholmentioning
confidence: 99%
“…Thousands of BAC clones are commercially available, and any of them can be used as FISH probes. Sugimura et al tested 100 BAC probes containing different kinase loci in a gastric, colorectal, and lung cancer detection sets (20 cases for each organ) by using tissue microarray (TMA)-FISH technology (Sugimura, Mori et al 2010). Sugimura et al found that unexpected kinase loci were amplified in a significant proportion of human common solid tumors (Sugimura, Mori et al 2010).…”
Section: Fluorescence In Situ Hybridization (Fish) Analysis Of Patholmentioning
confidence: 99%